On the degree of approximation by Gauss Weierstrass integrals - Huzoor H. Khan; Govind Ram (International Journal of Mathematics and Mathematical Sciences)
We obtain the degree of approximation of functions belonging to class Lip(ψ(u,v);p),   p>1 using the Gauss Weierstrass integral of the double Fourier series of f(x,y).